Pengaruh Kualitas Layanan terhadap Loyalitas Pelanggan Pengguna Kereta Api Commuter Line Jabodetabek Pada Stasiun Bogor - Herlin Widasiwi Setianingrum (Universitas Bina Sarana Informatika, 2018)
The users of Commuter Jabodetabek Train services are increased from year to year. However, this increase is not supported by the enhancement in the maximum service quality by PT. KAI Commuter Jabodetabek as sole organizer of Jabodetabek railway services. Maintaining customer loyalty is one of the good steps that can be applied by PT. KAI Commuter Jabodetabek. Hence, PT. KAI Commuter Jabodetabek is expected to be able to know what factors which can increase customer loyalty and also evaluate the factors that can decrease the level of customer loyalty, which can lead to better performance in order to achieve customer loyalty. Therefore, this research discusses about how Service Quality affects the Customer Loyalty of Jabodetabek Commuter Train’s users in Bogor Station. The design of this study is quantitative methods by making a regression test. The result shows that Quality of Service has a significance value of 0.003 which indicates that Service Quality positively and significantly affects the Customer Loyalty of Jabodetabek Commuter Train’s users in Bogor Station. Thus, to improve the Customer Loyalty of PT. KAI Commuter Jabodetabek, the company must improve the quality of its services.